PHYTOREMEDIATION OF NITRATE IN WATER BY A SEMI-AQUATIC VEGETABLE - Sundaralingam, T.; Gnanavelrajah, N. (Symposium Proceedings of The water Professionals’ Day, 2011)
The potential to phytoremediate water loaded with nitrate by Ipomoea aquatica was assessed in this study. Ten treatment combinations with five levels of nitrate N (0, 10, 20, 40 and 50 mg/L) and two levels of P (0 and 5mg/L) were treated to 3 liters of ground water. The design used was a two factor factorial with three replicates. Water was analyzed at weekly interval for nitrate N and P. Ipomoea.aquatica had the potential to remove nitrate N between 29.3-75% during three weeks in different treatments. In addition, 75%-83.3% of P was also removed from water. Total nitrogen and total phosphorus content in plants shows an increasing trend with increasing concentration of nutrients in water. The highest nitrate N in tissues of Ipomoea aquatica was recorded as 26.3 mg/kg, which was grown in water having 54 mg/L of nitrate. Therefore after remediation treatment Ipomoea aquatica could be used as vegetable without any harmful effects
Keywords: Nitrate; Lpomoea Aquatica; Phytoremediation